More than mobile - Addom, Benjamin K.; Tricarico, Daniele; Palmer, Tegan (Technical Centre for Agricultural and Rural Cooperation, 2015)
Mobile agriculture has contributed successfully to the current developments in ICT4Ag sector. This issue's guest editors predict further impact in the sector if cross-channel partnerships in ICT4Ag projects are achieved.